A boa-fé no direito tributário - Sampaio, Carlos Alberto Alves (2015)
This thesis aims to study the objective good faith in Tax Law. Using the deductive method of scientific research, we start from the theory of values as the highest level of abstraction, to get to the more specific level, which is the application of the law, through the analysis of concrete cases arising in the jurisprudence of judicial and administrative courts. Throughout the development of the work, we address several aspects of legal phenomenology we consider it essential to reach our conclusions, such as the interaction of axiology in major jusfilosóficas currents; the concept of Tax Law; how the objective good faith fits in Tax Law; some of the legal dichotomies; identification of good faith in the Constitution of 1988 and the National Tax Code (Código Tributário Nacional); contradictory behaviors that undermine the objective good faith, proof and presumption of good faith, among others. The study is essentially dogmatic and not philosophical. We use some concepts and philosophical references only to coordinate the rationale for further substantiate the possible answers to the questions formulated. Proceeded so because good faith is a legal principle that is not expressly contemplated in the Tax Law, requiring us to bring to the fore the whys of consideration of objective good faith, only to then demonstrate how the institute is included in Tax Law . The conclusion of the work suggests that the objective good faith is present in Tax Law in its fullness, which can also be proven by the identification of conflicting behaviors in the cases analyzed, despite the case law in tax matters, yet consign show timidity in characterization of these behaviors, such as the venire contra factum proprium, tu quoque, supprressio e surrectio